Analisis Data Suhu, Konduktifitas, Dan Aliran Panas Untuk Menafsir Struktur Bawah Permukaan Daerah Air Putih Lebong Utara - Purwanto, Andik (GRADIEN : Jurnal Ilmiah MIPA, 2007)
The measurement had been conducted at 50cm depth on Air Putih’s area, which is used needle probe. Thetransient heating of needle probe is used to measure the thermal conductivity and shallow depth temperature. Thetemperatures that have been measured are 17.42-52.930 C and the highest value of heat flow that have been measuredis 0.55 W/ m. K. Temperature measurements at shallow depths contain useful information about features of thegeological structures in Air Putih area. Essentials similarity between thermal and magnetic prospecting make itpossible to apply to thermal prospecting modification of the rapid method characteristic point developed for magneticprospecting. The interpretation result, which is used characteristic points, is the upper edge location of anomaly at 12.13 m below the surface